Pelvic differences between brachycephalic and mesaticephalic cats and indirect pelvimetry assessment - Monteiro, C. L. B.; Campos, A. I. M.; Madeira, V. L. H.; Silva, H. V. R.; Freire, L. M. P.; Pinto, J. N.; Souza, L. P. de [UNESP]; Silva, L. D. M. da (British Veterinary Assoc, 2013)
Pelvic measurements were carried out in cats with various cranial conformations to (1) determine pelvic morphometry, (2) compare any pelvic differences with cranial conformation and gender and (3) determine whether body biometrics can be used to predict pelvic measurements. Thirteen brachycephalic and 14 mesaticephalic female cats and 17 brachycephalic and nine mesaticephalic male cats were used. Body and external pelvic measurements, as well as pelvic radiographs, were performed. Brachycephalic females all had external pelvic and radiographic measurements that were significantly smaller than those of the mesaticephalic females, including smaller pelvic inlet and outlet areas and a smaller pelvic canal shape. Brachycephalic females had wider and flatter heads than do mesaticephalic females. Similarly, brachycephalic males all have radiographic pelvic measurements that are smaller than those of mesaticephalic males. Males had larger pelvis measurements than did their female counterparts for both cranial types, and indirect pelvimetry did not demonstrate good predictive value in determining the internal pelvic measurements. Thus, we conclude that pelvic differences exist between genders and between brachycephalic and mesaticephalic cats. Furthermore, body biometric measurements do not have good predictive value for determining internal pelvic measurements.